(untitled) (Research, Society and Development, 2021)
Objectives: This study has as main objective to identify through quantitative and descriptive survey which are the most sold herbal medicines used for the treatment of constipation marketed by a drugstore in the city of Manaus. Methods: list which herbal medicines for constipation were sold in August 2019 to August 2020; present the types of herbal medicines that act on constipation; list the medicines that were sold for constipation and score the results if used rationally. This work is an exploratory and descriptive research conducted in a drugstore located in the city of Manaus, Amazonas. Results: the most sold herbal medicine for intestinal constipation was the medicine with the medicinal plants Senna alexandrina and Cassia fistula with 40% (Laboratory A), right after that which contained the medicinal plant Plantago ovata (35%), Senna alexandrina and Cassia fistula (Laboratory B) (13%) and Aloe ferox and Gentiana lutea (12%), between August 2019 to August 2020. Conclusion: irrational use of herbal medicines cause adverse side effects, however with proper dosage the results are positive.